Kontribusi Perspektif Ekonomi Feminis dalam Pendidikan Ekonomi Keluarga Suku Melayu Jambi untuk Menanamkan Perilaku Ekonomi Pancasila - Mayasari Mayasari (Jurnal Ilmiah Dikdaya, 2019)
The aims of this study was to determine the contribution of a feminist economic perspective in the family economic education of the Jambi Malay to instill the Pancasila economic life as seen from the mindset, attitude and behavior patterns. Research methods using qualitative methods with a phenomenological approach. The subjects of this study were housewives as key informants namely SHJ, RTW, RTSE, IDRI, SILSY, and FAU in providing economic education to embed Pancasila economic life. The results of this study are the contribution of a feminist economic perspective in this study is the perspective of housewives viewed from the mindset, attitude patterns, and behavior in family economic education teaches that it must prioritize adat bersendi syara’, syara’bersendi kitabullah that is combined with values -cultural values such as the value of helping to help, the value of togetherness, the value of cooperation, the value of responsibility, the value of surrender, the value of planning, the value of opportunity, and the value of hard work. These values are applied in carrying out economic life in both the family and community environment. Conclusion family economic education provided from the point of view of the Malay housewife has instilled the Pancasila economic behavior.